(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Love, then, whether for God or human being, is a desire to merge with, be one with the beloved. This contributes to an ambivalence of expression that has been fully exploited by the poet Jayadeva in his Gitagovinda to portray the love of Radha and Krishna. Viewed at one level the love is earthly, sensual and profane, while at another level it expresses the deepest Bhakti (devotion) of the human soul for the divine.